Clark the shark and the school sing - Hale, Bruce (I can read comics., 2021)
"Clark the Shark is excited about the School Sing! He can't wait to sing. La-la-laaa! But when Mrs. Inkydink asks the class to sing and dance at the same time, Clark discovers that doing two things at once can be really challenging!"--